Respostas
respondido por:
1
x +y = 16 (1) x + (-4) = 16
x -y = 8 (2) x -4 = 16
x = 16 + 4
(1) x = 16 -y x = 20
(2) 16 -y -y = 8
-2y = 8 -16
-2y = -8 S = { 20 ; -4 }
y = -8/-2
y = -4
Baseado nisso você consegue a resposta de tudo
x -y = 8 (2) x -4 = 16
x = 16 + 4
(1) x = 16 -y x = 20
(2) 16 -y -y = 8
-2y = 8 -16
-2y = -8 S = { 20 ; -4 }
y = -8/-2
y = -4
Baseado nisso você consegue a resposta de tudo
Perguntas similares
7 anos atrás
7 anos atrás
7 anos atrás
9 anos atrás
9 anos atrás
10 anos atrás